Minimalizem v sodobni slovenski kratki prozi - Perić Jezernik, Andreja (Jezik in slovstvo, 2005)
The article discusses minimalism in a narrow sense, as a literary direction witin the postmodern era. The main focus is placed on researching the features of Slovene minimalism as demonstrated in the collections of short prose written by Andrej Blatnik, Dušan Čater, Aleš Čar, and Polona Glavan.
Keywords: Blatnik, Andrej; Čar, Aleš; Čater, Dušan; Glavan; Glavan, Polona; kratka proza; literarne študije; minimalizem; Slovene literature; slovenska književnost